Exploring Factors Influencing Students’ Entrepreneurial Intention in Vocational Colleges Based on Structural Equation Modeling: Evidence From China - Fu, Xiaoqian; Yan, Tianming; Tian, Yumi; Niu, Xinchen; Xu, Xin; Wei, Yao; Hu, Qifan; Ouyang, Zhongming; Wu, Xueshi (Frontiers in Psychology, 2022)
With the proposal of "mass entrepreneurship, mass innovation" and other ideas, the demand for entrepreneurial talent in China is increasing, but the supply of entrepreneurial talent is far behind demand. Consistent with the theory of social cognition and planned behavior, this study outlines a conceptual model including entrepreneurial intention, emotional competency, entrepreneurial self-efficacy, entrepreneurial attitude, entrepreneurial education, and subjective norms. A structural equation model was applied through a questionnaire survey of 382 vocational college students in Jiangxi province to test the relationship between the constructs in the model. The results show that: first, entrepreneurial attitude, entrepreneurial education, entrepreneurial self-efficacy, and emotional competency have positive effects on entrepreneurial intention, while the positive effects of emotional competency and subjective norms on entrepreneurial intention are not supported. Second, a mediating role is played by entrepreneurial self-efficacy and entrepreneurial attitude in the association between entrepreneurial intention and entrepreneurial education. Third, entrepreneurial self-efficacy and entrepreneurial attitude play mediating roles in the relationship between entrepreneurial intention and emotional competency. Some implications for entrepreneurial intentions for schools and students were discussed.